2020
DOI: 10.1038/s41598-020-64090-5
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Assisted Fabrication of Perovskite Solar Cells

Abstract: This paper presents the results of a combined experimental and analytical/computational study of the effects of pressure on photoconversion efficiencies of perovskite solar cells (PSCs). First, an analytical model is used to predict the effects of pressure on interfacial contact in the multilayered structures of PSCs. The PSCs are then fabricated before applying a range of pressures to the devices to improve their interfacial surface contacts. The results show that the photoconversion efficiencies of PSCs incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…Figure 7a-e presents the cross-sectional SEM images of the perovskite multilayers for applied pressures between 0 MPa and 10 MPa. We observed a signi cant decrease in grain-boundary defects or voids as the applied pressures increased from 0 MPa to 10 MPa, leading to closely packed grains that can improve both e ciency and stability of PSCs 19,22,29 . However, we observed patches of damaged grains at the top of the perovskite lms at 10 MPa (Fig.…”
Section: Moderate Pressure Lowers Defect Densitymentioning
confidence: 83%
See 1 more Smart Citation
“…Figure 7a-e presents the cross-sectional SEM images of the perovskite multilayers for applied pressures between 0 MPa and 10 MPa. We observed a signi cant decrease in grain-boundary defects or voids as the applied pressures increased from 0 MPa to 10 MPa, leading to closely packed grains that can improve both e ciency and stability of PSCs 19,22,29 . However, we observed patches of damaged grains at the top of the perovskite lms at 10 MPa (Fig.…”
Section: Moderate Pressure Lowers Defect Densitymentioning
confidence: 83%
“…The use of pressure has been shown to improve optoelectronic properties of perovskite lms [18][19][20][21] . In particular, the application of moderate pressure, during the fabrication of PSCs, has also been shown to improve interfacial surface contacts in multilayered structures of mixed-halide methylammonium perovskite solar cells, leading to enhanced e ciencies 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The study equally observed that productivity is very important for Nigeria ports growth. To a very large Oyewole et al(2020) extent the findings discovered that cargo throughputs are positively affected by the operations of Nigerian sea-ports. The study further observed that the quality of interaction between staff and customers become positive for the growth of cargo throughputs in Nigerian sea port.…”
Section: Discussion Of Findingsmentioning
confidence: 98%
“…DHL/Cisco (2015) defined resources as stocks of available factors that are owned or controlled by the firm. Based on previous studies; ICT resources in this study are defined Oyewole et al(2020) as a multidimensional term which integrates software and hardware which enhance telecommunication functions. These infrastructure (application, data, server and network), ICT personnel (people who posed technical know-how), ICT capital (cost of implementing and running ICT in an organization).…”
Section: Resource Based Theorymentioning
confidence: 99%
See 1 more Smart Citation